2020
DOI: 10.1136/bmjopen-2020-037290
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity patterns in a representative sample of adolescents from the largest city in Latin America: a cross-sectional study in Sao Paulo

Abstract: ObjectivesWe examined the patterns of total and domain-specific physical activity (PA) by sex, socioeconomic status and maternal education level in adolescents from Sao Paulo city, Brazil.DesignCross-sectional study.ParticipantsWe included a representative sample of 2682 (52.2% boys) adolescents aged 14–15 years from public and private schools in Sao Paulo, 2017. Socioeconomic status was assessed using a wealth index derived from principal component analysis. Descriptive analyses evaluated differences in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
0
23
2
Order By: Relevance
“…5 27 28 In comparison with several countries, the prevalence of selected behavioural and metabolic risk factors in India was much lower among adolescents. [29][30][31] The prevalence of binge drinking among those aged 10-19 years was 56% in Denmark, 35% in European countries, 17.7% in the USA, 10.3% in Korea, 8% in Iceland and 7.1% in Hong Kong. 29 More than 70% of boys and girls aged 10-19 years were doing insufficient physical activity across the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 27 28 In comparison with several countries, the prevalence of selected behavioural and metabolic risk factors in India was much lower among adolescents. [29][30][31] The prevalence of binge drinking among those aged 10-19 years was 56% in Denmark, 35% in European countries, 17.7% in the USA, 10.3% in Korea, 8% in Iceland and 7.1% in Hong Kong. 29 More than 70% of boys and girls aged 10-19 years were doing insufficient physical activity across the world.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The prevalence of obesity was 21% in the USA, 15% in the United Arab Emirates, 9% in the UK and China. 31 However, aggressive redressal to modify these unhealthy behavioural indices in India when at much lower proportions could have major benefits in controlling and tackling NCDs before they attain higher proportions in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar to other megacities in low- and middle-income countries, Sao Paulo has faced a fast-paced an unplanned urban growth 7 , 8 . These changes in the city’s urban environment are likely to impact physical activity 9 , 10 , as demonstrated by our previous study which showed that only 12.7% of adolescents from Sao Paulo engaged in sufficient physical activity 9 .…”
Section: Introductionmentioning
confidence: 92%
“…São Paulo has been described as a metropolis with a large and disorganized urban expansion. In recent years, there has been an increase in violence and a reduction of open public spaces 5,9 . These facts may explain the higher prevalence of physical inactivity in its population compared to other regions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with current PA recommendations, or even PA performance in continuous periods of at least 10 minutes per week, is absolutely essential to improve health and prevent chronic non-communicable diseases in all age groups, ethnicities and levels of schooling 1 . However, evidence 4,5 has shown that some population strata have greater opportunities to reach the recommendations for the practice of PA. In Brazil, the Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (VIGITEL) has revealed that men, and those with 9 years or more of schooling, practice more leisure PA than women and those with 8 or less years of schooling 4 .…”
Section: Introductionmentioning
confidence: 99%